Brillouin resonance broadening due to structural variations in nanoscale waveguides. (4th February 2016) - Wolff, C; Laer, R Van; Steel, M J; Eggleton, B J; Poulton, C G
Abstract: We study the impact of structural variations (that is slowly varying geometry aberrations and internal strain fields) on the width and shape of the stimulated Brillouin scattering (SBS) resonance in nanoscale waveguides. We find that they lead to an inhomogeneous resonance broadening through two distinct mechanisms: firstly, the acoustic frequency is directly influenced via mechanical nonlinearities; secondly, the optical wave numbers are influenced via the opto-mechanical nonlinearity leading to an additional acoustic frequency shift via the phase-matching condition. We find that this second mechanism is proportional to the opto-mechanical coupling and, hence, related to the SBS-gain itself. It is absent in intra-mode forward SBS, while it plays a significant role in backward scattering. In backward SBS increasing the opto-acoustic overlap beyond a threshold defined by the fabrication tolerances will therefore no longer yield the expected quadratic increase in overall Stokes amplification. Finally, we illustrate in a numerical example that in backward SBS and inter-mode forward SBS the existence of two broadening mechanisms with opposite sign also opens the possibility to compensate the effect of geometry-induced broadening. Our results can be transferred to other micro- and nano-structured waveguide geometries such as photonic crystal fibres.